Including practical experience in teaching results in deeper understanding - Amdi Williams, Charlotte (Improving University Science Teaching and Learning, 2023)
“Tell me and I’ll forget; show me and I may remember; involve me and I’ll understand.” – Chinese Proverb. The topic of this paper is the value of animal research and practical experience in particularly in the animal science and veterinary degrees. Focus will be on the master level course "Animal Production Science" and the value of gaining practical experience by visiting a farm.